The Efforts Of The Algerian State To Support Small And Medium-sized Enterprises “smes” In Order To Reduce Unemployment During The Period (2013-2019) - A Detailed Look At The Organisms In Charge Of Support - - Kidaouene, Abou Bakr Essedik (جامعة الوادي - University of Eloued, 2021)
This study aims to clarify the efforts made by the Algerian state to support SMEs in order to reduce unemployment, through the interpretation of the various statistics related to SMEs and unemployment, in addition to giving a detailed look at the organisms authorized by law to supervise the work of SMEs in Algeria. We used the deductive approach in order to explain the concepts related to SMEs and unemployment, we also used the inductive method in order to interpret the statistics related to SMEs and unemployment in Algeria. This study concluded that all unemployment rates from 2013 to 2019 were more than 10 and that the Algerian state has established three organisms (ANADE, ANGEM and FGAR), whose mission is to supervise and follow up the activity of SMEs.
مقال
Keywords: SMEs, Unemployment, Organisms, Efforts ; ;Algeria.